Enhanced fatigue reliability analysis of additively manufactured 316L stainless steel components - Zhengwei Cheng; Yongfeng Fang; Kong Fah Tee (AIP Advances)
Additively manufactured 316L stainless steel structural components are increasingly utilized across industries, necessitating accurate fatigue reliability assessments. This study develops a comprehensive approach to evaluate the fatigue reliability of such components. First, the stress–life relationship under cyclic loading is analyzed, providing stress calculation formulas for various fatigue lifespans. The residual strength degradation across three fatigue life stages is quantified, yielding values of 512.96 MPa at 800 cycles (1000 fatigue life), 463.27 MPa at 2500 cycles (3000 fatigue life), and 412.26 MPa at 5000 cycles (6000 fatigue life). Next, the fatigue reliability at each stage is determined using the first-order second-moment method, with reliability values of 0.9999, 0.9997, and 0.9291, respectively. The overall fatigue life reliability is computed using a series system approach, resulting in a final reliability of 0.9291. The proposed methodology is practical and user-friendly, making it suitable for real-world engineering applications.